Polysomnographic insights into the attention-deficit/hyperactivity disorder and obstructive sleep apnea connection in children - Lacki, Olga; Slaven, James; Rushton, Jerry; Rao, Harish; Thompson, Rohan; Jalou, Hasnaa; Bandyopadhyay, Anuja (Frontiers in Sleep, 2024)
Introduction: There is a high prevalence of sleep disturbances and disorders such as obstructive sleep apnea (OSA) in children with attention-deficit hyperactivity disorder (ADHD), though this relationship remains poorly characterized by objective measures. Polysomnographic studies (PSGs) on sleep disruptions in ADHD have yielded inconsistent results. Few have studied polysomnograms in stimulant-medicated versus non-medicated children with ADHD+/-OSA. This study aimed to elucidate pathognomonic polysomnographic sleep disturbances in children diagnosed with ADHD+/-OSA. Methods: Medical charts and polysomnograms were retrospectively reviewed for children ages 4-18 who underwent overnight polysomnography at a tertiary care center from 2019-2022. ADHD diagnosis was determined by ICD code F90, and OSA was defined by apnea-hypopnea indices (AHI) ≥5 events/hour. Four groups were evaluated: children without OSA or ADHD, children with OSA alone, children with ADHD alone, and children with ADHD+OSA. Statistical analyses identified significant differences among variables of interest. Results: 4,013 children met the study criteria. 2,372 children were without OSA and without ADHD (59.1%), 1,197 with OSA alone (29.8%), 333 with ADHD alone (8.3%), and 111 with ADHD and OSA (2.8%). Insomnia (ICD code G47.00) was prevalent in children with ADHD alone. However, they exhibited significantly better sleep efficiency (SE), than children with OSA alone, and SE did not significantly differ from the other groups. No significant difference in periodic limb movements (PLMs) was found across all groups. The above results held true even after correcting for stimulant usage. Conclusion: The increased frequency of clinical insomnia diagnoses in children with ADHD is not associated with any traditional parameters on polysomnogram. Innovative subclinical polysomnographic biomarkers are needed to identify sleep characteristics unique to ADHD. In children with both ADHD and OSA, PSG results do not reveal any distinctive sleep disturbances which cannot be better explained by OSA. These findings underscore the importance of screening for OSA in patients with ADHD and clinically assessing for other sleep concerns.